2013
DOI: 10.1136/amiajnl-2012-001263
|View full text |Cite
|
Sign up to set email alerts
|

Online disease management of diabetes: Engaging and Motivating Patients Online With Enhanced Resources-Diabetes (EMPOWER-D), a randomized controlled trial

Abstract: A nurse-led, multidisciplinary health team can manage a population of diabetic patients in an online disease management program. INT patients achieved greater decreases in A1C at 6 months than UC patients, but the differences were not sustained at 12 months. More INT than UC patients achieved improvement in A1C (>0.5% decrease). Trial registered in clinical trials.gov: #NCT00542204.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
303
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 212 publications
(314 citation statements)
references
References 25 publications
3
303
0
8
Order By: Relevance
“…The mean age of all participants ranged from 46 to 71 years. Ten studies (13,14,15,16,17,18,19,20,21,22) limited inclusion criteria to participants 1240 records identified through searches 899 records after duplicates removed 800 excluded based on abstracts.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean age of all participants ranged from 46 to 71 years. Ten studies (13,14,15,16,17,18,19,20,21,22) limited inclusion criteria to participants 1240 records identified through searches 899 records after duplicates removed 800 excluded based on abstracts.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Most studies reported improvement in HbA1c. Four studies (19,22,23,24) scored A for quality, nine (13,14,15,17,18,20,25,26,27) Fig. 2).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
See 1 more Smart Citation
“…Demand for better healthcare services is increasing while human and fiscal resources are decreasing (Duckett & Willcox, 2011). These challenges have exposed the fragility of healthcare systems and their infrastructure further; and emphases the need to establish a reliable and coherent plan to deal with these challenges (Tang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of transforming healthcare information from paper-based 1 It is important to note here that the name of the e-health solution was changed from PCEHR to MyHealth Record in 2015. To be systems to electronic health record systems have been very well documented; however, numerous social and technical e-health adaptation and implementation barriers have been reported in literature (AndrĂ© et al, 2008;Avgerou, 2008;Bernstein et al, 2007;Boonstra & Broekhuis, 2010;HFMA, 2006;Kennedy, 2011;Liu et al, 2011;Tang et al, 2013;Thweatt & Kleiner, 2007;Trudel, 2010). Previous reports call for the use of an EHR for better health information sharing and for more efficient healthcare delivery with more successful healthcare outcomes (Deloitte, 2008;Fiscella & Geiger, 2006;Gill, 2010;HĂ€yrinen et al, 2008;NHHRC, 2009;Wiljer et al, 2008).…”
Section: Introductionmentioning
confidence: 99%